Analisis Sistem Informasi Akuntansi Penggajian Dan Pengupahan Pada Sebuah Perusahaan - Ery Suryanti; Hendra Lesmana; Husni Mubarok; Puspa Fortuna Zulfa (LPPM UBSI Kampus Kota Tegal, 2023)
The payroll and wages system is made to make it easier for financial officers who have the responsibility to provide salaries or wages to employees. The data used in the process of providing employee work results includes the division of tasks and responsibilities in work as well as accounting records that must be owned by the company so that what employees receive is in accordance with their work results. The purpose of this study is to find out whether the payroll and wage system at this finance company is running well. This study uses data collection methods including: observation, interviews, and literature study. Data analysis in research is a descriptive analysis of the results of research that has been done, so it can be concluded that the finance company has run a very good system. The documents used in payroll and wages are sufficient so that the process of giving salaries and wages to employees runs well because the systems and documents really support company activities. The completeness of the documents made by the company is in accordance with the theory of the payroll and wage accounting system and the accounting records and financial bookkeeping that are used are appropriate so that when distributing payroll and wages the employees do not experience difficulties. The bookkeeping in the company, such as general journals and employee earning cards, is proof of giving employee work results according to the rules that apply to the company.